The Effect of External Debt on Emissions from Coal Consumption: Evidence from Turkey - Bese, Emrah; Friday, H. Swint (International Journal of Energy Economics and Policy, 2022)
This paper analyzes the effect of external debt on emissions from coal consumption per capita for Turkey for the period 1970 to 2020 through gross domestic per capita and square of gross domestic per capita. Results confirm that coal Kuznets curve for Turkey but the effect of external debt on emissions from coal consumption per capita is insignificant and negative. Further causality is not analyzed since the main of the study is to analyze the effect of external debt on emissions from coal consumption. Although the effect of external debt on emissions is insignificant and negative, Turkey’s investments for clean energy sources to diversify its energy resources should be continued.